Coupling a novel spiro-rhodamine B lactam derivative to Fe3O4 nanoparticles for visual detection of free copper ions with high sensitivity and specificity1. Issue 57 (25th June 2015) - Zhang, Hongyan; Zeng, Xiaoxue; Chen, Danlong; Guo, Ying; Jiang, Wenjing; Xu, Liangjun; Fu, FengFu
<x xml:space="preserve">Abstract</x> A novel spiro-rhodamine B lactam derivative, which can be coupled to Fe3O4 NPs and act as a Cu2+-selective visual sensor is reported. It can be used to directly detect as little as 50 nM of Cu2+ in river or tap water by only naked-eye observation.